SMART SOCIETY 5.0: THE DIGITAL LITERACY READINESS OF THE ENGLISH TEACHERS - Putri Maharani, Anak Agung; Wersi Murtini, Ni Made; Putu Arsana, Anak Agung (University of Kuningan, 2023)
Along with the rapid development of technology integrated within English language teaching, English teachers are necessitated to be digitally literate. In the attempt to be digitally literate, they need to acquire technical and pedagogical skills representing their readiness to integrate digital technology efficiently and effectively into the teaching learning process. This study, therefore, aimed at determining the digital literacy readiness level of the English teachers, to discover the differences between male and female English teachers’ digital literacy readiness and to probe the factors that affect the English teachers’ digital literacy readiness. The respondents were 33 English teachers currently working both in public and private high schools in Denpasar, Bali. Then, to address the issue, a mixed-method design was used. A questionnaire, an interview, and a focus group discussion were all conducted. Descriptive statistical analysis was used to examine the collected quantitative data; meanwhile, the qualitative analysis, encompassing data collection, data reduction, data presentation, and conclusion, was used to assess the collected qualitative data. It was found that the digital literacy readiness level of the English teachers was adequate. Specifically, based on gender, male and female English teachers were different in their readiness. They also identified 2 major factors affecting their digital literacy readiness.